(3oZQQ GdHdGZIs - (3gdGd GdUCHjA , gdGd Hf GdeMSf Hf EHQGgje Hf gdGd GdMQGfj, CHh GdMSjf , CHh GdMSf,J (B448 (3g` s
(3ChdgG (B:s
(3CeG HYO aGf Ghd eG GYedJ ajg GdbQGFM hYdbJ Hg GdGacGQ GddhGbM s
(3BNQgG (B:s
(3hGNQS dSGf GdbGOM hGOGe MeO GdMGeO hhGUd ZjX GdMGSO s
(3CKHJ Ydi GdeNWhWI YfhGf NGWF hNdJ ef GSe GdeDdas
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3JJab aj ChdgG eY GdfNSI GdChdi HGNJdGa aj HYV GdCdaGX hJJab aj BNQgG hJRjO gPg NGJeI ddUGHF s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B151s
Keywords: (3GdCOHs